Effect of Various Proteins on Different Molecular Weight Proanthocyanidin Fractions of Red Wine during Wine Fining - Cosme, Fernanda (2022)
The effect of several proteins on three main wine proanthocyanidin containing fractions with the mean degree of polymerization (mDP) of 1.5 (FI), 3.4 (FII), and 4.9 (FIII) was studied. Although casein and potassium caseinate showed similar molecular weight (MW) distribution, casein decreased the FI fraction more than the twice as effectively as potassium caseinate. A gelatin with a medium MW polydispersion induced a similar decrease (~20%) in all tannin fractions. A gelatin with low MW primarily removed the tannin fractions of lower mDP (FI and FII), while a gelatin with a higher MW had a minor effect (5%) on the fraction of higher mDP (FIII). Neither of the two studied isinglasses reduced the FII fraction. The tannins of FI and FIII were removed by swim bladder isinglass twice as effectively as by fish skin isinglass. For the mDP of fined wines, egg albumin induced a decrease on mDP of 24% for the more polymerized tannin fraction (FIII); although within all assays there was a decrease ranging from 6 to 14%